2019
DOI: 10.3389/fendo.2019.00360
|View full text |Cite
|
Sign up to set email alerts
|

Chordin-Like 1 Improves Osteogenesis of Bone Marrow Mesenchymal Stem Cells Through Enhancing BMP4-SMAD Pathway

Abstract: Chordin-like 1 (CHRDL1) is a secreted glycoprotein with repeated cysteine-rich domains, which can bind to BMPs family ligands. Although it has been reported to play important roles in several systems, the exact roles of CHRDL1 on human bone mesenchymal stem cells (hBMSCs) osteogenesis remain to be explored. The present study aimed to investigate the roles of CHRDL1 on the osteogenic differentiation of hBMSCs and the underlying molecular mechanisms. We found that CHRDL1 was upregulated during hBMSCs osteogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…p-Smad1/5/8 and Smad4 oligomerize to form a complex, which is transported into the nucleus to act as a transcription factor. Then, the expression of Runx2 and other osteogenic factors can be stimulated [44,45]. In this study, we also found that rhBMP-4 had a significant promoting effect on osteogenic differentiation of BMSCs from T2DM patients, and this effect was achieved via the BMP-4/Smad/Runx2 axis.…”
Section: Fold Changesupporting
confidence: 60%
“…p-Smad1/5/8 and Smad4 oligomerize to form a complex, which is transported into the nucleus to act as a transcription factor. Then, the expression of Runx2 and other osteogenic factors can be stimulated [44,45]. In this study, we also found that rhBMP-4 had a significant promoting effect on osteogenic differentiation of BMSCs from T2DM patients, and this effect was achieved via the BMP-4/Smad/Runx2 axis.…”
Section: Fold Changesupporting
confidence: 60%
“…SPP1 gene codes for osteopontin, the protein that is involved in the attachment of osteoclasts to the mineralized bone matrix. CHRDL1 protein has recently been shown to improve osteogenesis of bone marrow mesenchymal stem cells [ 26 ]. CNN1 gene also plays a role in osteoblast and osteoclast function and formation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, findings supported the relationship between the two genes and highlighted their role in different OI types and bone mineralization ( 50 ). Moreover, rescue experiments have proved to be an effective tool in recovering protein function, complementing the results obtained in gene manipulation studies ( 51 ).…”
Section: Validation Of Genetic Findingsmentioning
confidence: 95%